Lactoferrin Influence on the Course of Suppurative Corneal Ulcer - A. V. Kolesnikov; E. R. Nemtsova; M. M. Shishkin; A. V. Shchul’kin; O. I. Barenina; I. V. Kirsanova (Oftalʹmologiâ)
Research justification. Corneal ulcer is a common corneal pathology dangerous because of its complications, which occur in 2.5–37.9 % of cases despite modern treatment. Thus, the development of novel methods improving the results of corneal ulcer treatment is very important.Research objective was to evaluate the efficacy of lactoferrin-based therapy for experimental suppurative corneal ulcer.Material and methods. The study was performed in male chinchilla rabbits. Three intact rabbits (6 eyes) were used as control animals. Staphylococcus suppurative corneal ulcer was modeled in both eyes of 63 experimental animals. These rabbits were randomized into three groups. The first group was administered placebo therapy, the second group received antibacterial therapy, and the third group — instillations of lactoferrin. The area of ulcerative lesion was used as the measure of the therapeutic efficacy of the treatment. Then, a histological study was performed, and microsamples were photographed with LOMO TC-500 digital camera (Russia).Results. Lactoferrin instillations resulted in reliable increase in the number of transfers from infiltration stage to epithelization stage, decrease in the percentage of ulcerations, and in the proportion of critical thinning of the cornea, as well as decrease in the proportion of perforations. However, it was noticed that lactoferrin treatment when continued after the end of epithelization process resulted in excessive formation of opaque scar tissue.Conclusion. Local administration of lactoferrin stimulates the epithelium regeneration and the formation of the connective tissue and thus prevents the development of complications of suppurative corneal ulcer. However, the identified excessive formation of opaque scar tissue in lactoferrin treatment lasting too long has to be taken into consideration when developing the optimal scheme for lactoferrin treatment.